Oud Batavia as a heritage site within Jakarta: Tourist revisit intentions - Maulina, Anita; Sukoco, Iwan; Hermanto, Bambang; Kostini, Nenden; Rahmawati, Nur Fitri; Hartono, Hartono (Turyzm/Tourism, 2024)
The main objective of this study is to explore the dynamics of heritage tourism in Oud Batavia, the Old City of Jakarta, specifically focusing on perceived price, perceived authenticity and perceived value, and how they influence tourist satisfaction and revisit intentions. By using a quantitative design, data was collected from 406 valid responses through a questionnaire distributed in the Old City. The findings confirmed positive and significant relationships highlighting the importance of preserving historical buildings and emphasizing the role of perceived factors in enhancing the overall tourist experience. The study contributes valuable insights for stakeholders, urging the Jakarta city government and the Ministry of Tourism to focus on preserving cultural heritage buildings and employ adaptive reuse strategies to increase tourist visits. The limitations of the study include its exclusive focus on domestic tourists in the Old City of Jakarta, suggesting avenues for future research to explore broader topics such as city branding and foreign tourist perspectives. The study concludes with recommendations for strategies to commercialize historical tourist destinations and a call for United Nations Educational, Scientific and Cultural Organization recognition of the Old City as a world historical heritage site.